Synthesis of a Five-Membered Ring Derived from Pariazoline and Evaluation of its Bactericidal Activity - Al-Mouqdady , Omar D.H.; Abdulkareem, Athir Ibrahim; Ali, Arwa Falih; Saleh , Mohammed Jwher; Saleh , Jamil Nadhem (American Journal of Biomedicine and Pharmacy, 2025)
Pyrazole is a fundamental building block containing two nearby nitrogen atoms and a five-membered heterocyclic structure. Pyrazoles are extensively employed as versatile frameworks in several chemical industry domains, such as agriculture and medicine. The significance of pyrazoles and their many biological activities—such as antituberculosis, antibacterial, antifungal, anti-inflammatory, anticancer, and antidiabetic roles—have been well discussed in earlier reviews. They have therefore garnered a great deal of interest from scholars. In this work, chalcone-based compounds were used as the nucleus in typical sublimation reactions with hydrated hydrazine to create new pyrazole compounds. Physical measurements, proton nuclear magnetic resonance spectroscopy, and infrared spectroscopy were used to verify the integrity of these molecules. Using amoxicillin as the antibiotic, their bacteriological activity against two Gram-positive and Gram-negative bacteria was also evaluated.